Clinical effectiveness of drop-in mental health services in paediatric healthcare settings: a non-randomised multi-site study for children, young people and their families - Anna Roach; Sophie Bennett; Isobel Heyman; Anna Coughtrey; Neha Batura; Lina Gonzalez; Nicki Astle; Rebekah Coates; Jessie Drinkwater; Rebecca Evans; Una Frederick; Michael Groszmann; et al. (BMC Health Services Research)
Abstract Background Despite the high prevalence of mental health disorders in children and young people with long-term health conditions, access to timely and effective treatment is often difficult. This study aimed to evaluate the clinical effectiveness of drop-in mental health services for young people with long-term health conditions and their families at six paediatric healthcare settings in England. Methods This was a prospective non-randomised single-arm multi-centre interventional study. Young people up to 25 years old with a long-term health condition, and their families were eligible. The primary outcome was the change in the total difficulties score on the Strengths and Difficulties Questionnaire between baseline and 6 months. Interventions provided were standard evidence-based low intensity cognitive-behaviour therapy, onward referral or signposting. Secondary outcomes included quality of life, depression, anxiety, satisfaction with services and cost. Results Accessing the drop-in services led to significant reductions in emotional and behavioural symptoms (p < 0.01; Cohen’s d = 0.39) and improved quality of life (p < 0.01; Cohen’s d = 0.44). Parental depression and anxiety significantly improved (p < 0.01; Cohen’s d = 0.30 and d = 0.34). The average waiting time for an initial assessment was 13.42 days. High levels of satisfaction were reported. The cost per patient was approximately half the estimated cost of a typical course of psychological therapy. Conclusions Drop-in mental health services are effective and acceptable and can be delivered at low cost per patient for young people with long term conditions. This model of care is a feasible approach for increasing access to evidence-based mental health treatment in paediatric healthcare settings. Trial registration ISRCTN15063954, Registered on 9 December 2022.